Use of the Life Cycle Assessment (LCA) Method to Assess the Impact of Waste Processing at Black Soldier Fly (BSF) Sengkol, Central Lombok - Suripto; Supardiono; Putri, Nadea; Munstasyarah, Aula Sakinah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Black Soldier Fly (BSF) Sengkol is an organic waste management agency, which uses BSF or manggot as an organic waste biodegradation agent. The superiority of the process and results of processing organic waste using black soldier fly can be assessed using the Life Cycle Assessment (LCA) method. Student field work practice was carried out at BSF Sengkol using tutorial and practical methods with assistance from supervisors from BSF Sengkol and guidance from lecturer from the Environmental Science Department, Mataram University. The results showed that the participant understand and is skilled at assessing environmental impacts using the LCA method in waste processing at BSF Sengkol. The results of students' practical work show that CO2 emissions resulting directly from waste processing using BSF are much lower than with compost. According to LCA, waste processing by composting has twice the global warming potential compared to BSF waste processing.